A STUDY ON EFL LEARNERS’ ABILITY IN USING IRREGULER VERB THROUGH JOHNNY GRAMMAR WORD CHALLENGE APPLICATION - Pratiwi Samad; Nirma Paris (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2023)
Johnny Grammar Word Challenge Application become the test checker for students in mastering their skills of grammar. This research is aimed to determine the students’ ability and divide the students’ level of ability in using irregular verb through the application of Johnny Grammar Word Challenge on the sixth semester students of Universitas Sulawesi barat. The method used was qualitative-quantitative and the sample was drawn through random sampling. The data was collected from multiple choice test of Johnny Grammar by analyzing the data in qualitative and statically. The result shows that student’s ability in using irregular verb through Johnny Grammar Word Challenge Application categorized in “FAIRLY POOR” classification and the level of ability classified in “AVERAGE” category based on the measurement of quantitative description.